Sociodemographic and clinic factors associated with body mass index in patients with chronic kidney disease on hemodialysis - Ádria Juliane Lopes Melo Paiva; Mariana Pinheiro Campos; Luciana Pereira Pinto Dias; Karina Silva Cordeiro; Jorvana Stanislav Brasil Moreira; Isabel Cristina de Oliveira Almeida; Andréa Dias Reis; Nayra Anielly Cabral Cantanhede; Maria Rita Fonseca Dias; Mylenne Cardim Ferreira; Isabelle Christine Vieira da Silva Martins (Revista Brasileira de Obesidade, Nutrição e Emagrecimento, 2022)
Objective: To verify the factors associated with the Body Mass Index (BMI) in patients with chronic kidney disease on hemodialysis. Materials and methods: Cross-sectional analytical study conducted at a Hemodialysis Clinic in Belém-PA, Brazil. Socioeconomic data and physical activity practice were obtained through interviews with the application of a semi-structured questionnaire and biochemical and anthropometric data through consultation of patients' medical records. To identify the factors associated with BMI bivariate and multivariate analyses were performed with a hierarchical model. Results: Among the 91 patients evaluated 67.03% exhibited BMI < 24.9 kg/m2. The variables of occupation, physical activity and number of medications were significantly associated with BMI 25 kg/m2. Student patients were more likely not to have BMI 25 kg/m2 (PR=1.45; CI:4.87-4.34, p<0.001). On the other hand, patients who did not practice physical activity and who used 3 to 4 medications had a lower chance of not having BMI 25 kg/m2 (PR=0.48; CI:0.30-0.77, p=0.002; PR=0.23; CI: 0.77-0.70, p=0.009), respectively. Conclusion: Most patients did not have a BMI of 25 kg/m2 and it remained associated with occupation, physical activity and the number of drugs consumed by patients with chronic kidney disease on hemodialysis.